Manajemen Resiko Pada Produk BSM Cicil Emas di Bank Syariah Mandiri (BSM) Kantor Cabang Sukarno Hatta Malang - Muslihati, Tk. Umar Johan & (Universitas Muhammadiyah Malang, 2017)
The purpose of this research is to know the mechanism of product BSM Gold Installments financing, the strategy used by Bank Syariah Mandiri in managing the risk, and the impact of the strategy implemented by Bank Syariah Mandiri. The method of collecting data used in this research is direct interviews to relevant sources and collection of supporting considered documents. The results of this observation indicate that: first, the risk management strategy in BSM Gold Installments can be separated to four stages: identifying risk, measuring risk, controlling risk and monitoring risk. Second, the implementation of risk management strategy of BSM Gold Installments has had a significant impact on the low of risk. In fact the selling price of BSM Gold Installment of Bank Syariah Mandiri increased every year. On March 2015, the price of one gram gold reach on Rp. 543,000 and increase up to Rp. 578,000 per gram on March 2017.